Sloppy craft : postdisciplinarity and the crafts - Paterson, Elaine Cheasley; Surette, Susan (Bloomsbury Academic, 2015)
Sloppy Craft: Postdisciplinarity and the Crafts brings together leading international artists and critics to explore the possibilities and limitations of the idea of 'sloppy craft' craft that is messy or unfinished looking in its execution or appearance, or both. The contributors address 'sloppiness' in contemporary art and craft practices including painting, weaving, sewing and ceramics, consider the importance of traditional concepts of skill, and the implications of sloppiness for a new 21st century emphasis on inter- and postdisciplinarity, as well as for activist, performance, queer an.